Sijamuwangi: A Utilization of Virtual Treasures as A Resource for Learning History - Rosidi, Moh Imron; Fitroh, Ismaul; Juniarti, Gita (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study is to know the historical heritage collection at the Blambangan Museum, Banyuwangi Regency through Sijamuwangi application media and its utilization for a history learning source. While the problems studied in this study are: (1) what items from the collection of historical heritage in the Blambangan Museum are available to be accessed by using Sijamuwangi application? (2) how to use Sijamuwangi application as a source of history learning?. The research method applied in this study is literature method where the research material/research data needed are obtained from the library source in forms of books, documents, journals, encyclopaedias, articles and other source related to this study. According to the research results, the Blambangan Museum that integrated to the Sijamuwangi application collects a large amount of historical relics which can be utilized as a source of historical learning to learn about development of the social life, government, and culture during the period of Hindu-Buddha kingdoms in Indonesia.